MELACAK KONSEP KONVERSI AGAMA - Nasril Nasril (Universitas Islam Negeri Imam Bonjol Padang, 2015)
In general, religious conversion can be interpreted to change religion or to convert. Conversion is a spiritual growth or development containing a significant change in direction, the attitude towards religious teachings and actions. Conversion of religion shows that a sudden change of emotion to get the guidance of Allah, has occurred, which may be very deep or shallow. Such changes may occur gradually. It is a difficulty to measure and examine the facts of the conversion. It is similar with other psychic facts.